Competing Claims: Religious Affiliation and African Americans' Intolerance of Homosexuals. Issue 6 (12th May 2017) - Ledet, Richard
ABSTRACT: Literature on religion and political intolerance indicates competing expectations about how Black Protestant church affiliation affects African Americans' attitudes about civil liberties. On the one hand, Black Protestant theology emphasizes personal freedom and social justice, factors generally linked to more tolerant attitudes. On the other hand, Black Protestants tend to be conservative on family and social issues, factors often linked to intolerance of gays and lesbians. Data from the General Social Survey are used to examine the influence of religious group identification, as well as other relevant aspects of religiosity, on political intolerance among African Americans. Results indicate that although other aspects of religion (beliefs and behaviors) help explain variation in political intolerance, Black Protestant church affiliation has no relationship with attitudes about the civil liberties of homosexuals. However, additional tests show that Black Protestant church affiliation significantly predicts intolerance of other target groups (atheists and racists).